Teste de um Programa de Intervenção para Aumento do Equilíbrio Trabalho-Vida Pessoal: um estudo de aceitabilidade - Guiducci, Luiza Perches (Universidade Federal de São Carlos, 2023)
Difficulties in reconciling the demands of work and personal life can harm people’s perceptions of well-being and increase psychological stress. Although it is common for Brazilian workers to face these difficulties, there are few programs aimed at helping them to improve the balance between these areas of their lives. To address this problem, a program focused on training cognitive and emotional regulation skills was developed, based on previous programs reported in the literature, as a way to help people improve the balance between work and personal life. However, this program needs to be evaluated. In the present study, the objective was to evaluate the acceptability of the program when offered in an in-person format. In this format, the program consists of five modules, each lasting approximately two hours. Thirteen people between the ages of 24 and 57, including 5 men and 8 women, all with paid employment and moderate to high levels of work-life balance difficulties, completed the pre-test. After each session, participants completed a questionnaire to assess the acceptability of the activities proposed in each module, in order to identify possible areas for improvement. Quantitative data were examined using descriptive statistical analyses. Content analysis procedures were used to examine responses to open-ended questions, to identify positive comments, difficulties, and suggestions regarding the program. Some of the key findings were a retention rate of 92.8% (one person started but did not complete the program) and an attendance rate of 97.4% at the weekly sessions, indicating good acceptance of the program. Based on responses to the acceptability questionnaire, participants indicated very little difficulty in understanding the terms used and ease in understanding the language used in the program. In response to the open-ended questions, a few participants reported some difficulties, such as the speed of the training activities. The main limitations of the study involve the composition of the participant sample: they had high levels of education, and most had previous experience with psychotherapy, which could contribute to greater ease in understanding the program. Considering the overall results, the main recommendation for improving the program for the app format is to increase participants' control over the pace of training activities, before proceeding to a study of the effects of the program.
Testing an Intervention Program to Increase Work-Life Balance: an acceptability study
Keywords: Equilíbrio trabalho-vida; Atenção plena; Aceitabilidade; Regulação da atenção; Regulação emocional; Work-life balance; Emotion regulation; Acceptability; Attention regulation; CIENCIAS HUMANAS::PSICOLOGIA